KONFLIK RUMAH IBADAH (Studi Kasus Relokasi Gereja HKBP Desa Laut Dendang) - Arifinsyah, Arifinsyah; Fitriani, F (UIN Sumatera Utara Medan, 2019)
The conflict of establishment a place of worship is often an obstacle in efforts to create religious harmony. Not infrequently found in the establishment a place of worship experiencing problems, because the problem a place of worship is something that very sensitive and often triggers conflict. The purpose of this study to describe the problems that trigger conflict and analyzing conflict resolution mechanisms a HKBP church. This study uses qualitative-descriptive methods, namely research efforts that are based on the methodology in studying the phenomenon of conflicts the places of worship found in Indonesia. This study uses a sociology religion approach, which seeks to pay attention to the patterns of interaction of religious communities that cause conflict in the midst of Muslim and Christian communities. Based on the results of the research this conflict was caused by excessive religious emotions from local youth, the rejection of Muslims on the existence of the HKBP church which has disturbed the local community, there is a feeling that the position of the mosque can be threatened with a church whose buildings are more magnificent and the problem of establishing a house of worship that does not meet the requirements in the regulation of the Minister of Religion. In an effort to create harmony, the community should be open and intensify dialogue in various ways and be inclusive and instill tolerance in socio-religious activities.